الملائمة المناخية في العراق وامكانية استخدامها في تربية حشرة الجندي الاسود البروتينية - صائب احمد, ضياء (Journal of College of Education, 2019)
Climate elements and phenomena affect the lives of all living organisms and very severe climatic conditions sometimes lead to the destruction of living organisms and that man can not control the climate only if the size of the place is very small it can be controlled in terms of temperature and humidity as in the case of greenhouses used in Agriculture as well as breeding insect black soldier. It is known that insects may be beneficial, including harmful and some of them live in one place and lack in another place depending on climatic conditions and can be breeding some of them in their environment if they provide the right climates, and the insect is a black soldier rich in protein and can be used to feed fields Fish and poultry or as organic fertilizer for the soil.It is possible to raise the insect in Iraq, knowing that its habitat in southeastern North America and characterized by climate and permanent rain and warm atmosphere does not need breeding a large area of ​​size (1) m2 and in this case we can provide them with the climate suitable for breeding and thus reduce the import or manufacture of feed for fish or chicken Their arrangement does not require many costs, and they require materials such as those used in nurseries (greenhouses) and sawdust to provide a humid atmosphere always sprayed on sawdust as well as food waste and food to feed them.